Metagenomics for Gut Microbes - Kumavath, Ranjith N. (IntechOpen, 2018)
This book focuses on metagenomics for gut microbiomes. The host is deprived of various benefits derived from the numerous gut microbes for food metabolism and health. However, polysaccharides such as cellulose, xylans, resistant starch, and inulin that are found in vegetables in our diet are digested by certain species that colonize the intestines. In contrast, metagenomic studies that reiterate microbiome intrinsic factors from particular communities and lifestyles and are extremely important for bacterial communities traveling over a long distance have entered a new era. Predominantly to understand the behavior of organisms and their action in a host, next-generation sequencing will provide a new insight into analyzing the livestock industry, agriculture, and human health risks and will consider for future development novel therapies for various diseases through identification of advanced tools. Hence, the book will give more precise information on the role of gut microbiomes in the host.